دراسة لحالة انتحار وفق مقاربة نفسية اجتماعية من خلال تطبيق اختبار منيسوتا متعدد الأوجه MMPI-2 - مليوح، خليدة Meliouh, Khalidah (جامعة محمد خيضر بسكرة, 2017)
تختلف أشكال مظاهر العنف حسب التوظيفات النفسية المتكونة خلال حياة الفرد داخل أسرته، فالأسرة تعد اللبنة الأساسية في تكوين بنية شخصية للفرد، وأي اختلال في أنماط الاتصال الأسري تؤثر على تشكيل هذه البنية، خاصة إذا كانت متمثلة بعدة أنماط متناقضة، هنا الفرد لا يستطيع إدراكها، ونتيجة عدم إدراك هذه الطبيعة العلائقية ستؤثر في الفرد ذاته والمجتمع الحضري، وهذا ما سنتناوله من خلال دراسة حالة انتحار بالتركيز على عامل التصدع الأسري الطلاق الذي يعد مشكل اجتماعي، وأثره في تكوين بنية ذهانيه للحالة والتي ظهرت في اضطراب ذهاني وهو ثنائي القطب، والذي تم إثباته من خلال اختبار منيسوتا متعدد الأوجه للشخصية .MMPI-2
Forms of manifestations of violence vary according to the psychological investments formed through the individual life within the family, the family is the basic building block in the formation of character structure of the individual, and any disruption in patterns of family communication affect the formation of this structure, especially if it is represented by a number of contradictory patterns, here the individual can not be recognized, As a result of lack of awareness of this relational nature will affect the same individual and the urban community, and this is taken up by a case of suicide by focusing on cracking family divorce, which is the problem of social worker study, and its impact in the formation of psychotic situation structure which appeared in a psychotic disorder and is bipolar, and that has been proven through a multi-faceted personality MMPI-2 Minnesota test.
Keywords: الانتحار -- الأسرة -- الاتصال الأسري -- التصدع الأسري -- الاضطراب الذهاني -- اختبار مينسوتا متعدد الأوجه